Comunicação na sala de aula: A perspetiva do ensino exploratório da matemática - Guerreiro, António (2016)
This paper aims at answering to the challenge of thinking about the communication that occurs in the mathematics classroom. We disagree with the simplistic view of communication as a tool for knowledge transfer (from teacher to students); instead, we assume communication as a process of interaction, in which mathematical knowledge is socially constructed. Such a vision of communication in the mathematics classroom resonates with the processes of production and communication of mathematical knowledge that take place in the scientific field and the human community’s daily acting (when using mathematical ideas). Thus, changes are needed in mathematics teaching, particularly regarding the teacher’s and the students’ roles. Inquiry-based mathematics teaching is appointed as a privileged way to, supported by a set of fundamental communicative actions, create productive learning environments, which involve students’ work in challenging mathematical tasks, solving them and discussing the approaches taken, and culminate in the institutionalization of mathematical knowledge.